Pelatihan Akuntansi EMKM Industri Kerupuk Ujungpangkah Kabupaten Gresik - Widi Hidayat; Tri Ratnawati (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy. However, MSME players often face obstacles in preparing financial reports in accordance with applicable accounting standards. The application of the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) is a solution to improve the quality of MSME financial reports. This training aims to analyze the effectiveness of SAK EMKM-based accounting training in improving the understanding and skills of MSME actors in preparing financial reports. The training was conducted using interactive methods, accompanied by practical exercises and mentoring. The results of the training show that SAK EMKM-based accounting training is effective in improving the understanding and skills of MSME actors in preparing financial reports according to standards. The training materials include an introduction to accounting, the accounting cycle, preparation of financial statements according to SAK EMKM, and interpretation of financial statements for business decision making. The resulting financial statements consist of a profit and loss statement and a statement of financial position. The implementation of SAK EMKM is expected to improve the quality of MSME financial statements, so as to encourage sustainable business growth and increase access to formal financing.